The Research of Mortar Components Mixing Process - Popov, Stanislav; Shpylka, Andrii; Gnitko, Sergiy (International Journal of Engineering and Technology, 2018)
During the theoretical calculations of the power level consumed by the mortar mixer drive when mixing constructional mortar components, it is proposed to use the movement resistance specific coefficient. The developed method and a series of researches on an experimental test bench allowed to determine its numerical values when mixing cement-sand, lime-sand and complex mortars of various composition and lowability. The interpolated diagram of the consumed power of the band-screw operating device drive has been obtained, which has allowed to understand more deeply the technological process, as well as its characteristic stages and modes.Â Â